Analisis Faktor-Faktor yang Berhubungan dengan Keberhasilan Mahasiswa Program Profesi Ners - Marisa Manik; Christine Sommers; Kie Saputra; Eric Jobiliong (Fakultas Keperawatan Universitas Andalas, 2026)
It is essential that admitted nursing students complete their degrees and provide safe, high-quality patient care. Identifying factors that may predict student success helps determine the resources needed to support students both academically and psychosocially. This study examined the relationship between selected variables and scores on the Indonesian try-out for the National Nurse Competency Exam using a quantitative descriptive design. Statistical comparisons explored differences in grit scores, calling scores, reasons for wanting to be a nurse, and try-out scores. Two hundred seventy-nine students completed the online form. Regression analysis was used to analyze data and find correlations among experience, attributes, and academic variables. The first-semester GPA, admission scores in Mathematics and Bahasa Indonesia, motivations for becoming a nurse, grit scores, and BCS presence in the calling score were significant predictors of the try-out score. These factors all positively influenced the try-out score. In contrast, the BCS presence variable in the calling score had a negative effect on the try-out score. This suggests that when a student scores high in BCS presence, they tend to receive a lower score on the try-out. Of the seven reasons for wanting to become a nurse, only one showed positive significance in the try-out score, relating to a personal decision or calling. The admission process for nursing students should consider Math and Bahasa Indonesia skills, along with assessments of grit and motivation to become a nurse. Nursing programs must identify the most suitable approaches that best support nursing students.